Employment impacts of cleaner production: evidence from a German study using case studies and surveys - Friedhelm Pfeiffer; Klaus Rennings (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
The study assesses net employment effects of technical progress which can be expected by the ongoing transition from end-of-pipe technologies towards cleaner production. Empirical evidence is presented on the basis of case studies and panel data including a telephone survey in German industry. The main result ist that cleaner production leads in more firms to a net creation of jobs than end-of-pipe technologies. However, eco-innovations like other innovations tend to require higher qualification. Thus, the demand for skilled and high-skilled labour rises while the demand for unskilled labour decreases. The results imply that supporting cleaner production is not in conflict with labour market policy. Synergies are identified, they are however small and specific. Thus, technology policy in general and supporting cleaner production in particular can not be expected to give substantial contributions to the solution of mass unemployment in Germany without using additional instruments (e.g. concerning a reduction of labour costs, increasing flexibility of labour markets).
Keywords: 330; Umweltschutz; Umwelttechnik; Innovation; Technischer Fortschritt; Beschäftigungseffekt; Industrielle Umweltbelastung; Deutschland